Breaking the Chain of Materials Designers; Peter L Berger's Social Interpretation Perspective - Cian Ibnu Sina; Ikha Rahardiantini (International Journal of Nusantara Islam, 2019)
This paper aims to examine the mentoring model in an effort to Break the Substance Chain Designer from the Perspective of Social Interpretation Peter L Berger. The study of efforts to break the chain of designer substances tries to approach phenomenology and social construction in Peter L Berger's theory of former drug addicts in Haurpanggung Village, Tarogong Kidul District, Garut Regency. This analysis is based on qualitative data analysis, namely data that is sourced from words and actions. The research strategy used is a narrative strategy, using in-depth interviews with research subjects (respondents). As for the findings in the field that 8 out of 10 drug addicts who have been rehabilitated return to addicts with a new type of drug, namely designer substances, meaning that 80% fail after rehabilitation. However, through an empathic mentoring approach based on communication and geographic mutation, this can be continued continuously and produce total success.